GAME 3D PENGENALAN HADIS DENGAN MENGGUNAKAN TEKNIK PEMBELAJARAN IJMALI - Zulkiram, Muhammad; Dzikri, Afdhol; Gustin, Oktavianto (Pusat Penelitian dan Pengabdian Masyarakat, Politeknik Negeri Batam, 2021)
This paper discusses the development of a 3D game as a medium to improve the method of learning hadiths with Ijmali method and aims to measure the level of interest and desire of teenagers to study Hadith using the game. Ijmali method explains Hadiths in a clear, concise, and direct way. The game development is carried out using the Waterfall method. The software used for the development is Unity 3D. The evaluation was then carried out using questionnaires that consists of two stages. In the first stage, the experts were asked for their opinion about the game. Next, the questionnaire was distributed to the target respondents. Based on the result in the first testing stage, the lowest value is the Relevance aspect. Based on the result in the second testing stage, the lowest value is Usability. This shows that the game should have been designed with a lower level of difficulty to suit children aged 13-15 years. However, overall, the hadiths used in the game are valid and suitable for the students. It can be concluded that the use of the Ijmali technique as a hadith learning technique is quite effective for students.